2010
DOI: 10.1186/1472-6750-10-57
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-induced solid state instabilities in α-chymotrypsin and their reduction through chemical glycosylation

Abstract: BackgroundProtein instability remains the main factor limiting the development of protein therapeutics. The fragile nature (structurally and chemically) of proteins makes them susceptible to detrimental events during processing, storage, and delivery. To overcome this, proteins are often formulated in the solid-state which combines superior stability properties with reduced operational costs. Nevertheless, solid protein pharmaceuticals can also suffer from instability problems due to moisture sorption. Chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Figure 5a shows the CD spectrum of CT in buffer solutions depicting distinguished maxima at 254, 289 and 296 nm, corresponding to the presence of Trp residues of CT. These results are very well correlated with earlier reported results by various research groups [29], [49], [54]. Decrease in intensity of peaks can be probably due to the treatment of CT with plasma jet; changes being more prominent at 286 nm.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 5a shows the CD spectrum of CT in buffer solutions depicting distinguished maxima at 254, 289 and 296 nm, corresponding to the presence of Trp residues of CT. These results are very well correlated with earlier reported results by various research groups [29], [49], [54]. Decrease in intensity of peaks can be probably due to the treatment of CT with plasma jet; changes being more prominent at 286 nm.…”
Section: Resultssupporting
confidence: 92%
“…The far-UV CD spectrum (200–240 nm) of the enzyme indicated that CT has a peculiar secondary structure in presence of all of the above co-solvents discussed. CT is a type of all-β protein characterized by a CD spectrum, which resembles that of a random coil conformation [29], [54]. Crystal structure data showed that this kind of protein consists of antiparallel pleated β-sheets which are either highly distorted or form very short irregular strands [29].The same was reflected with APPJ action as well.…”
Section: Resultsmentioning
confidence: 97%
“…Increased water content also favors a higher conformational mobility of the protein molecule [11], making it more susceptible to chemical modifications. It was reported that increased water levels could lead to higher intermolecular disulfide exchange reactions forming covalent aggregates [10,11,13,16]. From a physical perspective, the residual water can act as a medium and plasticizer, resulting in decreased glass transition temperatures and increased crystallization rates [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The water content of lyophilized protein formulations often determines the chemical and physical stability of the solid state of protein powders [3,9]. The general trend is that the product integrity improves with decreasing water content, and various studies are available reporting on the effect of increased residual water amounts on physical and chemical instabilities [9][10][11], including recent publications on moisture-induced aggregation of freeze-dried proteins [12][13][14][15][16]. Breen et al reported growing Asp isomerization with increasing water content [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation